Two-year follow-up study of elderly residents in S. Paulo, Brazil: methodology and preliminary results Estudo de seguimento por dois anos de idosos residentes em São Paulo, Brasil: metodologia e resultados preliminares - Luiz R. Ramos; João Toniolo N.; Maysa S. Cendoroglo; Jacqueline T. Garcia; Myrian S. Najas; Monica Perracini; Cristina R. Paola; Fania C. Santos; Tereza Bilton; Simone J. Ebel; Maria B. M. Macedo; Clineu M. Almada F.; et al. (Universidade de São Paulo, 1998)
INTRODUCTION: Previous cross-sectional studies have shown a high prevalence of chronic disease and disability among the elderly. Given Brazils rapid aging process and the obvious consequences of the growing number of old people with chronic diseases and associated disabilities for the provision of health services, a need was felt for a study that would overcome the limitations of cross-sectional data and shed some light on the main factors determining whether a person will live longer and free of disabling diseases, the so-called successful aging. The methodology of the first follow-up study of elderly residents in Brazil is presented. METHOD: The profile of the initial cohort is compared with previous cross-sectional data and an in-depth analysis of nonresponse is carried out in order to assess the validity of future longitudinal analysis. The EPIDOSO (Epidemiologia do Idoso) Study conducted a two-year follow-up of 1,667 elderly people (65+), living in S. Paulo. The study consisted of two waves, each consisting of household, clinical, and biochemical surveys. RESULTS AND CONCLUSIONS: In general, the initial cohort showed a similar profile to previous cross-sectional samples in S. Paulo. There was a majority of women, mostly widows, living in multigenerational households, and a high prevalence of chronic illnesses, psychiatric disturbances, and physical disabilities. Despite all the difficulties inherent in follow-up studies, there was a fairly low rate of nonresponse to the household survey after two years, which did not actually affect the representation of the cohort at the final household assessment, making unbiased longitudinal analysis possible. Concerning the clinical and blood sampling surveys, the respondents tended to be younger and less disabled than the nonrespondents, limiting the use of the clinical and laboratory data to longitudinal analysis aimed at a healthier cohort. It is worth mentioning that gender, education, family support, and socioeconomic status were not important determinants of nonresponse, as is often the case. INTRODUÇÃO: Estudos transversais recentes mostraram alta prevalência de doenças crônicas e incapacidades físicas entre idosos. Considerando o rápido processo de envelhecimento do Brasil e as conseqüências que esse aumento de idosos com doenças crônicas e incapacidades associadas acarretará para o sistema de saúde, fazia-se necessário estudo que pudesse superar as limitações dos dados transversais, permitindo determinar quais os fatores determinantes de uma vida longa e livre de doenças incapacitantes, o chamado envelhecimento bem sucedido. É apresentada a metodologia do primeiro estudo epidemiológico longitudinal com idosos residentes na comunidade, no Brasil. MÉTODO: O perfil do cohorte inicial é comparado com dados de estudos anteriores a com o perfil dos não respondentes para avaliar a validade de análises longitudinais futuras.O projeto EPIDOSO (Epidemiologia do Idoso) seguiu por dois anos 1.667 idosos (65+), residentes em São Paulo. Consistiu de duas ondas, cada qual com três inquéritos: domiciliar, clínico e laboratorial. RESULTADOS E CONCLUSÕES: O perfil da população não diferiu de estudos anteriores, mostrando maioria de mulheres, viúvas, vivendo em domicílios multigeracionais, com uma alta prevalência de doenças crônicas, distúrbios psiquiátricos e incapacidades físicas. A despeito de todas as dificuldades inerentes a um estudo longitudinal, o grupo de não-respondentes ao segundo inquérito domiciliar não diferiu significativamente dos respondentes, assegurando análises longitudinais livres desse tipo de viés. Em relação aos inquéritos clínico e laboratorial, os não-respondentes mostraram-se mais velhos e mais incapacitados que os respondentes, limitando o uso dos dados clínicos e laboratoriais a análises pertinentes a uma cohorte mais jovem e saudável. Sexo, educação, apoio familiar e nível socioeconômico não influenciaram de forma significativa a taxa de não - resposta, ao contrário do que se costuma verificar.